Perbandingan Pendekatan Laparoskopi dan Laparotomi dalam Penanganan Kasus Kehamilan Ektopik - Freddy Dinata; Natasya Theresia Simatupang (Universitas Pahlawan Tuanku Tambusai, 2025)
Ectopic pregnancy is a condition in which the product of conception is implanted outside the endometrial lining of the uterus. The primary treatment for ectopic pregnancy is surgical. The advantages of the laparoscopic approach in comparison to laparotomy remain a controversy. The present study is designed to conduct a comprehensive review of studies that compare laparoscopic and laparotomy methods for the treatment of ectopic pregnancy. In order to identify relevant studies published within the past decade, a search was implemented on PubMed and ScienceDirect. In the five studies that were included, laparoscopy was demonstrated to be associated with superior outcomes in terms of the estimated intraoperative blood loss, length of stay, and duration of surgery. Further research is necessary to assess the cost-effectiveness of laparoscopy in treating ectopic pregnancy, with the aim of providing further evidence to justify its use in various clinical settings.